ЕFFICACY AND AFTER-EFFECT OF HERBICIDE PREPARATIONS IN THE MAIZE-WHEAT CROP-ROTATION UNIT - Maya DIMITROVA; Shteliyana KALINOVA; Tonya GEORGIEVA; Plamen ZOROVSKI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the study was to trace the after-effect of soil and leaf herbicides applied in maize on the next crop in rotation – wheat. In a 4-year period were carried out field experiments. The efficacy and selectivity of herbicides in maize were traced. Visual observations of plants of wheat were conducted during various phenological phases of the crop: germination, first leaf displayed (BBCH-11), two leaves displayed (BBCH-12), tillering (BBCH-20), lactic maturity (BBCH-77). Manifestations of phytotoxicity on the wheat plants were not established. After-effect of the herbicides was traced and the formation of major quantitative traits: plant height, length of classes, number of classes, number of grains in the class and weight of grain in the class. By variance analysis of pooled data were analyzed signs and evidenced the differences compared to the untreated control. The differences between the variatns with treatment and the control are essential. This confirms the visual assessments about the lack of negative after-effect of Laudis OD, Lumax 538 SC, Elumis, Gardoprim plus Gold 500 SC, Wing P, Stellar, Casper 55 VG and Merlin flex, applied in maize, on the next crop in rotation.